Mesopancreas—Anatomical Insights and Its Implications for Diagnosis and Clinical and Surgical Practice - Florin-Mihail Filipoiu; Georgian-Theodor Badea; Mihaly Enyedi; Ștefan Oprea; Zoran-Florin Filipoiu; Daniela-Elena Gheoca Mutu (Diagnostics)
Background: The concept of mesopancreas is frequently discussed in the surgical literature as the neural pathway for metastatic spread in pancreatic head cancer. It generally refers to a retro-pancreatic plane that should be resected to reduce the incidence of regional metastases. However, this concept remains poorly defined, both embryologically and anatomically. Our objective was to establish a clear embryological and anatomical definition of the mesopancreas, making anatomical data more applicable in surgical practice. Methods: We examined seven cadavers (5 males, 2 females, aged 62–71) with no medical or surgical history, preserved in 9% formalin at Carol Davila University’s Anatomy Department. Regional dissections were performed in successive planes, highlighting the celiac ganglia and the associated network of neural connections that comprise the mesopancreas. Results: Our study defines the “mesopancreas” as remnants of primordial mesenteries that coalesced into the Treitz fascia. We identified its functional components as nerve fibers linking the celiac ganglia and superior mesenteric plexus to the pancreas, along with vascular structures, lymphatics, and connective and adipose tissue. These components likely contribute to regional metastasis in pancreatic head cancer. While resection of the mesopancreas could help prevent metastasis, its complex anatomy and proximity to major vessels pose significant surgical challenges. Conclusions: Based on our findings, we propose a plausible definition for the term “mesopancreas”. It encompasses the structures that originated as part of the primordial mesenteries, which subsequently coalesced, resulting in the formation of the Treitz fascia. In essence, the mesopancreas is the functional content of a former mesentery.